CENTRAL ASIA AND THE CAUCASUS IN IRAN’S FOREIGN POLICY STRATEGY 1991-2020 - Дияб аль-Ноймат, А.М. (Asian Journal "Steppe Panorama", 2025)
This article comes to present the stages of Iran's foreign political strategy in its relationship with the countries of Central Asia and the Caucasus from 1991 to 2019, and the importance of these relations in expanding Iran's interests and ensuring its economic and political interests in the region. In this case, the article clearly shows that Iran's interests are becoming a serious problem in the Central Asia and the Caucasus to the rapid growth in demand for natural fuels. In fact, Central Asia and the Caucasus are the regions where the geopolitics and competition between the United States and Iran are most influenced by their vast energy resources and strategic position. The author conclude that Central Asia and the Caucasus are of particular interest to the Iran, while Central Asia and the Caucasus is one of the best options for Russia, China, and the United States.